2016
DOI: 10.1002/chin.201612012
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Phase Relations in the Na2MoO4—Cs2MoO4 and Na2MoO4—Cs2MoO4 —ZnMoO4 Systems, Crystal Structures of Cs3Na(MoO4)2 and Cs3NaZn2(MoO4)4.

Abstract: Systems, Crystal Structures of Cs 3Na(MoO4)2 and Cs3NaZn2(MoO4)4. -In view of incomplete data, the binary systems Na 2MoO4-Cs2MoO4 and Na2MoO4-ZnMoO4 bounding the Na2MoO4-Cs2MoO4-ZnMoO4 phase system are reinvestigated by annealing appropriate amounts of monomolybdates (420-700 C, 50-200 h). The new intermediate compound Cs 3Na(MoO4)2 is found to melt incongruently at 510 C. It crystallizes with the glaserite type structure (triclinic, space group P3m1, Z = 1; powder XRD). The sub solidus phase relations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The above‐mentioned abundance of the alluaudite‐type among double molybdates of sodium and bivalent metals allows us hoping to continue the series Na 25 Cs 8 R 5 (MoO 4 ) 24 ( R = Fe, Sc, In) in the systems Na 2 MoO 4 –Cs 2 MoO 4 – M MoO 4 ( M = Mg, Mn, Co, Ni, Cu, Zn, Cd). However, our study of the system Na 2 MoO 4 –Cs 2 MoO 4 –ZnMoO 4 showed no similar phase and predominance of the solid solution Cs 6 Zn 5‐ x ⬜ 1‐ x Na 2 x (MoO 4 ) 8 (0 ≤ x ≤ 1) with the Cs 6 Zn 5 (MoO 4 ) 8 structure (sp. gr.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The above‐mentioned abundance of the alluaudite‐type among double molybdates of sodium and bivalent metals allows us hoping to continue the series Na 25 Cs 8 R 5 (MoO 4 ) 24 ( R = Fe, Sc, In) in the systems Na 2 MoO 4 –Cs 2 MoO 4 – M MoO 4 ( M = Mg, Mn, Co, Ni, Cu, Zn, Cd). However, our study of the system Na 2 MoO 4 –Cs 2 MoO 4 –ZnMoO 4 showed no similar phase and predominance of the solid solution Cs 6 Zn 5‐ x ⬜ 1‐ x Na 2 x (MoO 4 ) 8 (0 ≤ x ≤ 1) with the Cs 6 Zn 5 (MoO 4 ) 8 structure (sp. gr.…”
Section: Introductionmentioning
confidence: 65%
“…The subsolidus phase relations of the system Na 2 MoO 4 –Cs 2 MoO 4 –CoMoO 4 were determined using the methods of intersecting joins and “significant points” elaborated for the ternary systems with binary compounds in the boundary systems and described in in detail. The samples corresponding to eight selected significant points[34b] sufficient for inspecting phase compositions of all joins of the Na 2 MoO 4 –Cs 2 MoO 4 –CoMoO 4 system, were annealed at 480 °C for 200 h with daily intermittent grindings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation